Pengembangan Media TikTok untuk Meningkatkan Motivasi Belajar Seni Lukis Peserta Didik SMP - Dewi, Seryawati Kusuma; Prasetyo, Abdul Rahman (Jurnal Pendidikan dan Penciptaan Seni, 2025)
The painting learning in class IX at SMP Shalahuddin Malang is still traditional without interactive media, leading to low student motivation. This study aims to describe the learning needs related to low motivation, develop media based on TikTok effects, and present the results of media trials. Using the ADDIE development model, the research went through five stages: analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, document studies, expert validation, and product trials. The analysis results showed the need for a more interactive learning approach. The TikTok effect-based media developed using the Effect House app was deemed highly feasible, with material expert assessment at 84% and media expert assessment at 94%. Product trials scored an average of 86%, and this media increased student motivation by an average of 66%, with an N-Gain value of 81.12%. Observations by teachers and researchers showed an N-Gain motivation increase of 73.89%, rising by 78%. This study shows that TikTok effect-based media can be widely applied in educational institutions to support learning relevant to technological developments. This media not only boosts learning motivation but also provides an engaging and innovative learning experience, making it suitable for fostering students' creativity in digital-era art education.